Physical Human-Robot Interaction of a Robotic Exoskeleton By Admittance Control - Chenguang Yang (IEEE Transactions on Industrial Electronics, 2018)
In this paper, physical human-robot interaction (pHRI) approach is presented for the developed robotic exoskeleton using admittance control to deal with human subject's intention as well as the unknown inertia masses and moments in the robotic dynamics. Human subject's intention is represented by the reference trajectory when the robotic exoskeleton is complying with the external interaction force. Online estimation of the stiffness is employed to deal with the variable impedance property of the robotic exoskeleton. Admittance control is firstly presented based on the measured force in order to generate a reference trajectory in interaction tasks. Then adaptive control is proposed to deal with the uncertain robotic dynamics and a stability criterion can be obtained. Bounded errors are shown in the motion tracking while the robustness of the variable stiffness control is guaranteed. The experimental results indicate that the proposed control enables the human subjects to execute an admittance control task on the exoskeleton robot effectively.